Macro-elements K, Na, Cl, Mg, and Ca in body tissues of false killer whales (Pseudorca crassidens) from the Southern Ocean - Cáceres Saez, Iris; Haro, Daniela; Blank, Olivia; Aguayo Lobo, Anelio; Dougnac, Catherine; Arredondo, Cristóbal; Cappozzo, Humberto Luis; Ribeiro, Sergio (Polar Biology)
Macro-elements such as potassium (K), sodium (Na), chlorine (Cl), magnesium (Mg), and calcium (Ca) are essential in marine mammals’ nutrition. These elements are involved in physiological processes. Upon consumption, they are assimilated and accumulate in tissues. For the first time, they were detected in lung, spleen, liver, kidney, muscle, uterus, ovary, and testis of 5, and in skin of 12, stranded false killer whales (Pseudorca crassidens) in sub-Antarctic waters of the South Atlantic Ocean. Results showed that testis reached the highest potassium mean concentration, 1.62 (0.25) wt% dry weight (DW) (standard deviation in parentheses), followed by muscle, 1.11 (0.12) wt% DW, and decreasing in skin to 0.351 (0.098) wt% DW. Testis and lung exhibited among the highest sodium concentrations, with 0.96 (0.20) and 0.93 (0.18) wt% DW, respectively. Chlorine concentration was highest in testis, (1.55 wt% DW) followed by uterus (1.26 wt% DW) and kidney [1.13 (0.16) wt% DW]. Magnesium reached higher concentrations in uterus (0.134 wt% DW) and muscle [0.109 (0.054) wt% DW]. Calcium was higher in lung [0.230 (0.05) wt% DW] and kidney (0.149; 0.294 wt% DW). Hepatic levels of K, Na, Cl, and Mg in false killer whales are generally within the range of other studied species, while Ca levels are the highest reported. Macro-element concentration ranges were established for diverse tissues and organs of the false killer whale as the current best available baseline reference values for assessments of general condition. Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Haro, Daniela. Universidad Santo Tomás (ust); Fil: Blank, Olivia. No especifíca; Fil: Aguayo Lobo, Anelio. No especifíca; Fil: Dougnac, Catherine. Wildlife Conservation Society; Chile Fil: Arredondo, Cristóbal. Wildlife Conservation Society; Chile Fil: Cappozzo, Humberto Luis. Consejo ...